Shining a light on AIS Blackouts with maritime OSINT - Sage, Emerald Cara (Frontiers in Computer Science, 2023)
Maritime OSINT can be used to capture information, critical to business operations, including when electronic systems like Automatic Identification Systems (AIS) fail. AIS is used to identify vessels in maritime navigation, to plan shipping operations, and ensure safety. This data is collected and sold by global aggregators to maritime operators and industry stakeholders. However, AIS communications are vulnerable to malicious cyber activity, changing legal landscapes, adverse physical conditions, or intentional intervention. It is the latter we will focus on in this report. Often, we won’t understand the motivation behind a decision to either switch off or manipulate AIS data. However, this decision can have real world impacts, including on relationships between nation states, and the physical safety of maritime personnel. We believe maritime open-source intelligence (maritime OSINT) may represent an effective method to assist in the management of AIS failures. Maritime OSINT not only captures important maritime information when AIS fails, but it provides valuable context, giving us the who, what, and why for vessel operations. In our cast study, we will use maritime OSINT to track sanctioned Russian oil exports, demonstrating how OSINT can be used in this example to inform sanctions compliance programs.